Information sources on culinary tourism for France,Italy and Thailand. - Abdul Karim, Muhammad Shahrim; Leong, Jerold (Taylor & Francis, 2008)
In the present information age, customers may be overloaded with informa- tion from multiple media sources (Lurie 2004). Information search can be de- fined as “the motivated activation of knowledge stored in memory or acqui- sition of information from the environment” (Engel, Blackwell and Miniard 1995: 494). Based on the definition, information search behavior comprises internal and external sources (Beatty and Smith 1987). Specifically, internal information can be linked to individual, personal and previous experience. On-the-other-hand, external information search can be related to information from other outside sources, for example information in the print and electron- ic media, word-of-mouth, and marketing intermediaries (Beatty and Smith 1987; Engle, Blackwell and Miniard 1995). This study aims to explore the effects of information sources on travelers’ inten- tion to visit culinary destinations. The main purpose of this study was to explore the effects of information sources on travelers’ intention to visit three well established culinary destinations, i.e. France, Italy, and Thailand. These desti- nations were selected during the focus group session. Two research questions were developed for this study: a) What sources of information are considered most important to travelers interested in visiting a culinary destination?; and b) What is the moderating effect of demographic characteristics on the rela- tionship between information sources and travelers’ intention to visit?